PLAYING “GAMELAN” FOR DEPRESSION AMONG OLDER PEOPLE IN BPSTW ABIYOSO YOGYAKARTA: Terapi Memainkan Gamelan Untuk Penurunan Tingkat Depresi Pada Lansia Di PSTW Abiyoso Yogyakarta - Santoso, Nindita; Rohman, Muh. Fathoni; Mulyanti , Mulyanti (Jurnal Kesehatan Masa Depan, 2022)
Older people experience a decrease in physical, biological, psychological conditions, as well as changes in social and economic conditions. These changes will affect all aspects of life including health. Elderly people who do not get treatment for mental health problems will trigger depression. One of the easiest and inexpensive non-pharmacological therapies is to give therapy by playing gamelan instruments. This study aimed to determine the effect of playing gamelan instruments on the level of depression in the elderly at the Tresna Werdha Social Service Center Abiyoso, Yogyakarta. This research was a quasy-experiment with a one group pretest-posttest design. A sample of 28 elderly respondents was taken using a purposive sampling technique. The intervention was carried out 8 times with a duration of 20 minutes. The research instrument used was the Geriatric Depression Scale. The results of this study indicated that there is a significant difference in depression scores before and after giving the intervention in the form of playing gamelan instruments (p = 0.001) with an average decrease in value of 1.11. Health service providers are expected to use traditional music therapy in the form of gamelan to reduce depression levels in the elderly.